Seed based plant propagation algorithm for multiple travelling salesman problem - Kalaiarasi, S; Sriramya, P (International Journal of Engineering and Technology, 2018)
Multiple Travelling Salesman Problem is a complex problem in which route for a salesman is assigned to visit a city that has various hurdles such as congested road, damaged road, etc. In recent years biologically inspired algorithms are most widely used to solve many optimization problems. Here seed based plant propagation algorithm is applied for the multiple travelling salesman problem that is also a optimization problem, and the result is compared with a short-cut routing algorithm. The result shows that Seed based Propagation Algorithm is easy to implement since it has few parameters to be utilized and also time complexity is reduced when implemented in multiple travelling salesman problem.Â Â
Keywords: Multiple Travelling Salesman Problem; Seed Dispersal; Short Cut Routing; Plant Propagation Algorithm.